Gender-sensitive analysis of ICD indications in European heart failure guidelines. (19th May 2022) - Rilo, I; Beramendi Calero, JR; Quintas Ovejero, LAURA; Rengel Jimenez, AINHOA; Cea Primo, DANIEL; Hernandez De Alba, LEIRE; Nunez Rodriguez, ALVARO; Calvo Chumillas, SERGIO; Querejeta Iraola, RAMÓN
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Although there is evidence that women do not benefit as much as men from ICD implantation and receive a greater number of inappropriate discharges, the clinical practice guidelines for heart failure do not contemplate a different attitude taking into account gender. Objective: The aim of this study is to analyze the clinical trials and registries on which the recommendations of the guidelines are based. Methods: We selected in the bibliography of the 2021 European heart failure guidelines the registries and clinical essays and analyzed them attending to gender perspective according to the following questions: Is gender treated as a primary variable? Is gender treated as a secondary variable? Is there a differentiated analysis by sex? Are side effects described differently by sex ? What is the proportion of women in the study? Results: We analyzed 16 articles. The proportion of women is between 15 and 25%. Only 6 in 16 articles reported a differentiated analysis by sex and there was only one article that differentiated side effects according to sex. Among the studies that reported differentiated analysis by sex, two of then show that women didn`t benefit of the implantation of ICD. Conclusions: Gender analysis should be mandatory in all the clinical essays carried out in the future. Guidelines should consider different recommendations according to gender. Being excluded or infrarrepresented in studies could conditionate a discrimination to women not only now but also in the future when the algorithms of artificial intelligence condition the decisions we make in the different pathologies